👤

Cum se face exercitiul 4?

Cum Se Face Exercitiul 4 class=

Răspuns :

√(6-4√2)+√(6+4√2) =
=√(6-√32)+√(6+√32) =
=√[6+√(36-32)]/2 -√[6-√(36-32)]/2 + √[6+√(36-32)]/2 +√[6-√(36-32)]/2 =
 =√(6+√4)/2 -√(6-√4)/2 + √(6+√4)/2 +√(6-√4)/2 =
 =√(6+2)/2 -√(6-2)/2 + √(6+2)/2 +√(6-2)/2 =
=√8/2 -√4/2 + √8/2 +√4/2 =
=√4 -√2 + √4 +√2 =
=2+2=4

se foloseste formula radicalilor compusi
√(a+√b) =√[a+√(a²-b)]/2+√[a-√(a²-b)]/2
√(a-√b) =√[a+√(a²-b)]/2-√[a-√(a²-b)]/2





[tex] a^{3}+ b^{3}=(a+b)( a^{2}+ b^{2}-ab) =(a+b)((a+b)^2-2ab-ab)= \\ =(a+b)((a+b)^2-3ab)=10(100-3)=970 [/tex]